Chapter Leonardo da Vinci e il lago di Serravalle - Nieri, Ilaria (Territori, 2023)
Among his hydraulic designs, Leonardo planned the construction of an artificial lake in an area east of the castle of Vinci, his native village. The project, a surprising demonstration of his perfect knowledge of places where he lived, is illustrated in three drawings found and studied by Renzo Cianchi. Today, it is particularly interesting to analyze the feasibility of Leonardo's project, by chronologically translating it to the 21st century, namely in 2020. Based on an accurate hydrologic analysis, this paper aims at providing further insights on Leonardo's study, focusing on the feasibility of the dam.